Pemanfaatan Kecerdasan Buatan (AI) untuk Meningkatkan Efektivitas dalam Penyusunan dan Penulisan Karya Ilmiah Terhadap Mahasiswa Generasi Z Sekolah Tinggi Ilmu Ekonomi Bima Program Studi Manajemen - Muniarty, Puji; Rimawan, M; Ovriyadin, Ovriyadin; M Syukur Dwiriansyah (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to explore how artificial intelligence (AI), specifically ChatGPT, is utilized by students in the preparation and writing of scientific papers, and how it impacts their critical thinking skills. A descriptive qualitative approach combining literature review and interviews with students at the Sekolah Tinggi Ilmu Ekonomi Bima, which teaches a research methodology course, was used. Five informants were recruited. Information was obtained regarding ChatGPT usage patterns and students' perspectives on its contribution. Findings indicate that ChatGPT is generally used to outline papers, paraphrase, and check linguistic aspects such as grammar. Although this technology helps with efficiency, the quality of scientific papers assisted by ChatGPT remains a concern regarding originality, depth of analysis, and coherence of ideas. On the other hand, intelligent use of ChatGPT can support the development of critical thinking skills and creativity and facilitate students in completing scientific papers, especially in translating foreign terms. However, excessive reliance can actually weaken students' critical thinking skills. In addition, sometimes the use of ChatGPT in writing scientific papers can also result in violations of academic regulations and ethics. Therefore, it is necessary to use ChatGPT proportionally to maintain academic integrity and support a meaningful learning process.